DEVELOPMENT AND VALIDATION OF A RP-HPLC METHOD FOR THE SIMULTANEOUS ESTIMATION OF SILODOSIN & MIRABEGRON IN BULK AND PHARMACEUTICAL DOSAGE FORM - T.S ANEESA THAHASIN; R. KIRAN JYOTHI; MAHESH.M (The Bioscan, 2026)
A robust and sensitive reversed-phase HPLC method was developed and validated for simultaneous determination of silodosin and mirabegron in pharmaceutical formulations. Separation was achieved on a YMC-ODS column (200 × 4.6 mm, 5 µm) using a buffer:methanol (40:60, v/v) mobile phase at 1.0 mL/min on a Waters HPLC system, with UV detection at 227 nm, producing well-resolved, symmetric peaks. Validation following ICH Q2(R1) demonstrated excellent linearity (R² = 0.999) over 6.4–32 µg/mL for silodosin and 20–100 µg/mL for mirabegron. Mean recoveries were 98.25% and 98.64%, and assay results were 102.0% and 99.8%, indicating high accuracy. Precision (%RSD <2%) and recovery at 50%, 100%, and 150% levels (98–99%) confirmed method reproducibility and accuracy. LOD/LOQ values were 0.4/1.3 µg/mL for silodosin and 4.3/4.3 µg/mL for mirabegron, demonstrating good sensitivity. Robustness testing showed minor deliberate changes in chromatographic conditions did not affect performance.This validated RP-HPLC procedure is simple, precise, sensitive, and well suited for routine quality control of silodosin and mirabegron formulations.